2011
DOI: 10.1038/nn.2778
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the RNA targets and position-dependent splicing regulation by TDP-43

Abstract: TDP-43 is a predominantly nuclear RNA-binding protein that forms inclusion bodies in frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). The mRNA targets of TDP-43 in the human brain and its role in RNA processing are largely unknown. Using individual-nucleotide resolution UV-crosslinking and immunoprecipitation (iCLIP), we demonstrated that TDP-43 preferentially binds long clusters of UG-rich sequences in vivo. Analysis of TDP-43 RNA binding in FTLD-TDP brains revealed the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
1,129
5
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 974 publications
(1,247 citation statements)
references
References 38 publications
66
1,129
5
4
Order By: Relevance
“…To address whether the reduced RNA binding capacity in the RRM2mut was associated with changes in RNA binding specificity, we performed TDP‐43 iCLIP (Tollervey et al , 2011) on CNS tissue. As RRM2mut homozygotes are not viable, we performed iCLIP in embryonic brains for that strain.…”
Section: Resultsmentioning
confidence: 99%
“…To address whether the reduced RNA binding capacity in the RRM2mut was associated with changes in RNA binding specificity, we performed TDP‐43 iCLIP (Tollervey et al , 2011) on CNS tissue. As RRM2mut homozygotes are not viable, we performed iCLIP in embryonic brains for that strain.…”
Section: Resultsmentioning
confidence: 99%
“…TDP43 binds to and regulates thousands of RNA targets [13,14,[36][37][38], and is thus in a unique position to dramatically affect gene expression on a global scale. The RNA-binding domains of TDP43 and FUS are essential for toxicity in ALS model systems, testifying to the importance of RNA dysregulation in ALS pathogenesis [34,[39][40][41].…”
Section: Rna Expressionmentioning
confidence: 99%
“…The RNA-binding domains of TDP43 and FUS are essential for toxicity in ALS model systems, testifying to the importance of RNA dysregulation in ALS pathogenesis [34,[39][40][41]. Immunoprecipitation studies in murine brain [14], dissociated primary cortical neurons [37], and human brain [13] and cell lines [13,38] showed that TDP43 recognizes nearly one-thrid of all transcribed genes by binding to redundant GU-rich sequences [42]. While nuclear TDP43 binds preferentially to distal intronic sequences, cytoplasmic TDP43 recognizes more 3' untranslated region (UTR) binding sites [13].…”
Section: Rna Expressionmentioning
confidence: 99%
See 2 more Smart Citations